Association Between School Environment with Sedentary Behavior and Physical Activity Intensity in Children - De Moraes-Ferrari, G (Nature Research, 2023)
We examined the association between indicators of the school environment with sedentary behavior and different intensities of physical activity in children. The study that included 515 children (265 boys) aged 9–11 years old from public and private schools in the city of São Caetano do Sul. Sedentary behavior and different intensities of physical activity were evaluated with an accelerometer. Inside school environment (policies, supervision committee, extracurricular activities, breaks, and access to school facilities) was evaluated using a questionnaire. Policies and practice (β: 8.49; 95% CI: 3.62–13.36), supervision committee (5.42; 0.64–10.19), inter-school competitions (2.40, 2.25–2.55), breaks of 15–29 min/day (6.87; 2.20–10.75), and outdoor sports field (5.40; 0.37–10.44), were positively associated with moderate-to-vigorous-intensity physical activity. Furthermore, crossing guards (7.65; 3.00–12.30) were positively associated with moderate-to-vigorous-intensity physical activity. We concluded that an association was found between school environment indicators with higher levels of physical activity and greater odds of meeting physical activity guidelines. © 2023, The Author(s).